Synthesis and characterization in monkey of [(11)C]SP203 as a radioligand for imaging brain metabotropic glutamate 5 receptors - Siméon, Fabrice G. (Eur J Nucl Med Mol Imaging, 2012)
PURPOSE: [(18)F]SP203 (3-fluoro−5-(2− (2-([(18)F]fluoromethyl)-thiazol−4-yl)ethynyl)benzonitrile) is an effective high-affinity and selective radioligand for imaging metabotropic 5 receptors (mGluR5) in human brain with PET. To provide a radioligand that may be used for more than one scanning session in the same subject in a single day, we set out to label SP203 with shorter-lived (11)C (t(1/2)=20.4 min) and to characterize its behavior as a radioligand with PET in the monkey. METHODS: Iodo and bromo precursors were obtained by cross-coupling 2-fluoromethyl−4-((trimethylsilyl)ethynyl) −1,3-thia-zole with 3,5-diiodofluorobenzene and 3,5-dibromofluoroben-zene, respectively. Treatment of either precursor with [(11)C] cyanide ion rapidly gave [(11)C]SP203, which was purified with high-performance liquid chromatography. PET was used to measure the uptake of radioactivity in brain regions after injecting [(11)C]SP203 intravenously into rhesus monkeys at baseline and under conditions in which mGluR5 were blocked with 3-[ (2-methyl−1,3-thiazol−4-yl)ethynyl]pyridine (MTEP). The emergence of radiometabolites in monkey blood in vitro and in vivo was assessed with radio-HPLC. The stability of [(11)C]SP203 in human blood in vitro was also measured. RESULTS: The iodo precursor gave [(11)C]SP203 in higher radio-chemical yield (>98 %) than the bromo precursor (20–52 %). After intravenous administration of [(11)C]SP203 into three rhesus monkeys, radioactivity peaked early in brain (average 12.5 min) with a regional distribution in rank order of expected mGluR5 density. Peak uptake was followed by a steady decline. No radioactivity accumulated in the skull. In monkeys pretreated with MTEP before [(11)C]SP203 administration, radioactivity uptake in brain was again high but then declined more rapidly than in the baseline scan to a common low level. [(11)C]SP203 was unstable in monkey blood in vitro and in vivo, and gave predominantly less lipophilic radiometabolites. By contrast, [(11)C]SP203 was stable in human blood in vitro. CONCLUSION: [(11)C]SP203 emulates [(18)F]SP203 with regard to providing a sizeable mGluR5-specific signal in monkey brain, and advantageously avoids troublesome accumulation of radioactivity in bone. Although [(11)C]SP203 is unsuitable for mGluR5 quantification in monkey brain, its evaluation as a PET radioligand for studying human brain mGluR5 is nevertheless warranted.